2020
DOI: 10.1097/bpo.0000000000001618
|View full text |Cite
|
Sign up to set email alerts
|

External Validation of an Algorithm to Predict Adjacent Musculoskeletal Infection in Pediatric Patients With Septic Arthritis

Abstract: Background: Septic arthritis (SA) remains a potentially morbid disease in the pediatric population. Magnetic resonance imaging (MRI) is the most sensitive tool for recognizing associated osteomyelitis and intramuscular abscess, but is a limited resource. The aim of this study is to externally validate a previously developed algorithm (Rosenfeld and colleagues) to predict adjacent infection in pediatric patients diagnosed with SA. Methods: We identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Poor performance of the BSDS may be a consequence of the algorithm's development. The BSDS has been derived from logistic regression using a large number of variables (6) and subcategories (26) despite a relatively small patient cohort (n ¼ 65). Using odds ratios and coefficients from Appalanaidu et als.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor performance of the BSDS may be a consequence of the algorithm's development. The BSDS has been derived from logistic regression using a large number of variables (6) and subcategories (26) despite a relatively small patient cohort (n ¼ 65). Using odds ratios and coefficients from Appalanaidu et als.…”
Section: Discussionmentioning
confidence: 99%
“… 5 For example, previous research showed that algorithms to predict behaviour of paediatric septic arthritis developed in the Northern Hemisphere did not perform well in our region. 6 The aim of our study was to externally validate the BSDS on a larger and geographically separate cohort of patients.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, children who attend the emergency department in a delayed manner may be at increased risk of severe course of illness. 10 Potential limitations of this work include retrospective nature, small sample size, and selection bias. Given that each centre has variable disease outcomes the ratio of potential predictive factors to complication events can impact analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This in itself may be a risk for contiguous disease, allowing organisms to spread through adjacent tissues over time without active treatment. In summary, children who attend the emergency department in a delayed manner may be at increased risk of severe course of illness 10…”
Section: Discussionmentioning
confidence: 99%
“…Determining the presence of contiguous osteomyelitis in the presence of suspected septic arthritis is challenging 4 . Prediction algorithms have been proposed to guide the acquisition of magnetic resonance imaging (MRI) during septic arthritis treatment [5][6][7] . Some centers have taken the approach that MRI acquisition should be considered only after the child has failed to demonstrate adequate improvement following initial treatment of septic arthritis [7][8][9][10] .…”
mentioning
confidence: 99%